Gastric Metastases in Primary Breast Cancer: Case Report and Literature Review - Araújo, Luiz Henrique de Lima (2007)
Introduction: Breast cancer is the most common neoplasm in women. In Brazil, approximately 48,930 new cases are expected in the year 2006. Sites for metastases from primary breast cancer include lymph nodes, bones, bone marrow, lungs, liver, and central nervous system. Reports of gastric metastasis are rare in published series on advanced breast cancer. Upper gastrointestinal endoscopy is usually performed and shows a diffuse intramural infiltration similar to linitis plastica, found most commonly in cases presenting lobular carcinoma. A comparative histopathological study of mammary and gastrointestinal specimens is mandatory, but immunohistochemical techniques may also be useful. The prognosis is often reserved. Treatment is palliative, including systemic chemotherapy, hormonal therapy, and radiation therapy. Case report: A patient in adjuvant therapy for breast cancer with anastrozole presented with epigastric pain and weight loss. Physical examination revealed a palpable epigastric mass, and upper gastrointestinal endoscopy revealed an infiltrating lesion located at the antrum and corpus of the stomach. Histopathological examination confirmed metastatic ductal carcinoma with mucosecretory areas and "signet ring" cells (CK7-positive and CK20 and hormone receptor-negative). Since there were no other disease sites, the patient was treated with six cycles of docetaxel, leading to a complete gastric pathological response. Discussion: Although rare, gastric metastasis can involve high morbidity in patients with breast cancer and may respond to appropriate systemic antineoplastic therapy.